Pengaruh Latar Belakang Pendidikan Mahasiswa terhadap Motivasi dan Minat Pembelajaran Bahasa Arab - Rina Anjani; Fitrotul Hasanah; Nurul Hafizah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The difference in educational background of UIN Sultan Maulana Hasanuddin Banten students, especially between pesantren and public school graduates, becomes an obstacle in the learning process of intensive Arabic classes. Students who come from public schools often feel left behind compared to their friends who come from pesantren or Madrasah Aliyah. Therefore, it is important to conduct this study to examine the effect of pesantren graduates‘ background on motivation to learn Arabic, so as to provide a better understanding of the factors that influence students’ learning motivation. The researcher used a quantitative method with data collection through questionnaires. The collected data were analysed systematically to identify patterns and meanings related to the influence of pesantren education background on motivation to learn Arabic. The results showed a significant effect of boarding school education on students' motivation to learn Arabic. Thus, boarding school education background can increase motivation to learn Arabic. The implication is that educational institutions need to consider the background of students in designing effective learning methods. Future research is recommended to include additional variables that have the potential to influence Arabic language learning motivation.